Consciousness and creativity in artificial intellegence : the cognitive side of knowledge management - Johannessen, Jon-Arild (Emerald Publishing Limited, 2023)
With Industry 4.0 accelerating AI, synthetic knowledge and creativity, Consciousness and Creativity in Artificial Intelligence posits a central question: "Under what conditions can intelligent robots develop creativity?". Opening a new field of investigation for knowledge management at the organizational level, Johannessen discusses new theories around uncovering hidden knowledge, which is assumed to be the area of knowledge responsible for the emergence of creativity and innovation. Reflecting upon how intelligent robots can develop creativity, Consciousness and Creativity in Artificial Intelligence examines three classes of algorithms - linear, evolutionary and systemic. Consciousness and Creativity in Artificial Intelligence is a thought-provoking but accessible text appealing to those researching innovation, knowledge and creativity in organizations both now and in the future.--Resumé vydavatel
Keywords: umělá inteligence; počítače; inteligentní systémy; kreativita; artificial intelligence; computers; intelligent systems; creative ability; elektronické knihy; monografie; electronic books; monographs